2018
DOI: 10.22159/ajpcr.2018.v11i9.25361
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cosupplementation Therapy With Vitamins B9, B12, and D on Endothelial Dysfunction in Streptozotocin-Induced Diabetic Rats

Abstract: Objective: This study evaluated the effects of Vitamins D, B9, and B12 given individually or combined in ameliorating some biochemical parameters related to endothelial dysfunction in diabetic rats.Methods: A total of 50 Sprague-Dawley male rats were divided into five groups: Control, diabetic, diabetic received Vitamin D, diabetic received Vitamins B9 and B12, and diabetic received Vitamins B9, B12, and D. At the end of 6 weeks, the rats were sacrificed and a set of assays was carried out to determine: Fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a recent study of 2018 it was concluded that co-administration of Vitamins D, B9, and B12 exerted some antiatherosclerotic effects through inhibiting lipid peroxidation coupled with increasing aortic tissue nitric oxide (NO). These findings may have important uses and implications in the modulation and protection against diabetic endothelial dysfunction [42].…”
Section: Vitamin D and Diabetes Mellitusmentioning
confidence: 86%
“…In a recent study of 2018 it was concluded that co-administration of Vitamins D, B9, and B12 exerted some antiatherosclerotic effects through inhibiting lipid peroxidation coupled with increasing aortic tissue nitric oxide (NO). These findings may have important uses and implications in the modulation and protection against diabetic endothelial dysfunction [42].…”
Section: Vitamin D and Diabetes Mellitusmentioning
confidence: 86%